Water scarcity forcing rural Kenyan women to devise coping mechanisms - Onyango, Patricia; Zaremba, Haley Carter; Nchanji, Eileen; Guettou Djurfeldt, Nadia (2024)
In the past few years, most women and youths in Kilifi County have struggled with access to water for diverse activities due to climate change, limited networks, and income. Thus, access to and use of water is often negotiated and shaped by intrahousehold dynamics and government institutions. While women tasked to provide water for their families create networks to sustain access to water and diversify water sources. men move out for better jobs, and youths take up commercial water provision roles